Cooperative Knowledge Representation and Classification for Design Projects - Dai, Xinghang; Matta, Nada; Ducellier, Guillaume (Knowledge Discovery, Knowledge Engineering and Knowledge Management, 2015)
Design is a knowledge-intense activity. In design projects, both domain knowledge and cooperative knowledge are produced. Present knowledge engineering methods focus on how to extract and model expert knowledge, but cooperative knowledge that is produced in cooperative activities is usually ignored. In this paper, the cooperative knowledge in design projects is studied, and a cooperative knowledge representation structure as well as a framework to classify it is proposed.